Ab initio study of the low-lying states of PS molecule. (January 2023) - Xiao, Lidan; Xue, Jianlei; Liu, Yong; Yan, Bing
Highlights: MRCI+Q calculations are performed on PS including the SOC and CV effect. Potential energy curves and spectroscopic constants of bound states of PS are obtained. The transition properties including the TDMs, FCFs and radiative lifetime τ of 2 2 Π1/2 -X1 2 Π1/2, 2 2 Π3/2 -X2 2 Π3/2, 1 2 Σ − 1/2 -X1 2 Π3/2 and 1 2 Σ − 1/2 -X1 2 Π1/2 have been determined. Abstract: Quantum chemical calculations on the low-lying electronic states of PS correlating with the lowest four dissociation limits are performed by utilizing the internally contracted multireference configuration interaction method (icMRCI) with all-electron Gaussian basis sets. The potential energy curves (PECs) and spectroscopic constants of low-lying bound states are computed. It is of interest to compare the spectroscopic constants of low-lying bound states for the PS molecule with experimental and theoretical results. The detailed information on the properties of the emission 2 2 Π1/2 -X1 2 Π1/2, 2 2 Π3/2 -X2 2 Π3/2, 1 2 Σ − 1/2 -X1 2 Π3/2 and 1 2 Σ − 1/2 -X1 2 Π1/2 bands of PS system, including the transition dipole moments (TDMs), permanent dipole moments (PDMs), Franck-Condon factors (FCFs) and radiative lifetimes, has been identified. We first calculated the f value and radiative lifetime of this radical. Whether the C state is 1 2 Σ − or 1 2 Δ is discussed. According to the calculation results, it is confirmed that the experimental C state is redistributed to 1 2 Δ. Our study should be valuable for further experimental works understanding the spectroscopy and dynamics of the electronic excited states for PS.